Historical Persian recipes for paper dyes - Barkeshli, Mandana (Walter de Gruyter GmbH, 2016)
During the Taimurid (1370–1507 A.D.) and Safawid 1501–1736 A.D.) to Qajar periods (1785–1925 A.D.), Iranian masters introduced a number of paper dyes in order to prepare a suitable support for their calligraphies and paintings. This paper will discuss the different types of dyes and application techniques as described in Persian historical sources. Eighteen manuscripts from the thirteenth to the nineteenth century were selected and studied in detail; recipes were translated and categorized according to colour, materials and techniques in order to be able to draw comparisons. Studying these historical references not only adds a new dimension to the identification of materials used in manu- scripts and miniature paintings of the period under study, but also can help to preserve the colours by providing a better understanding of their composition, manufacture and use.